Towing icebergs to arid regions to reduce water scarcity - Alan Condron (Scientific Reports, 2023)
Abstract Expanding agriculture, rising global population, and shifts in climate are placing increasing demands on existing water resources, especially in regions currently experiencing extreme drought. Finding new and reliable water sources is an urgent challenge. A long-held idea is that icebergs could be towed to arid coastal regions and harvested to help alleviate water stress. Here, a numerical model is used to simulate the deterioration of icebergs towed to Cape Town, South Africa and the United Arab Emirates (UAE). Moved at a speed of 0.5 m/s, an iceberg able to reach Cape Town must be at least ~ 300 m long and ~ 200 m thick at its time of capture. An iceberg this size would only require ~ 1 to 2 vessels to move and would deliver ~ 2.4 million liters of water. Placing an insulating material around the same iceberg to inhibit wave-induced erosion results in 4.5 billion liters of deliverable water. To reach the UAE, an unprotected iceberg needs to be at least ~ 2000 m long and 600 m thick, or 1250 m long and 600 m thick if insulated from wave-induced erosion. Icebergs of these dimensions would require ~ 10 to 20 vessels to move. Results are discussed in terms of the size and number of icebergs needed to help alleviate drought. In theory, small icebergs can easily be moved to South Africa; the challenge is likely to be harvesting the water as icebergs left offshore in a subtropical environment melt after a few days to weeks.